Labour Tax Reform, The Good Jobs and the Bad Jobs. - Henrik Jacobsen Kleven; Peter Birch Sørensen (University of Copenhagen, Economic Policy Research Unit (EPRU), 1999)
We analyse recent proposals to shift the tax burden away from low-paid labour, assuming a dual labour market where the 'good' high-paying jobs are rationed. A shift in the tax burden from low-paid to high-paid workers has an ambiguous effect on the level of aggregate employment while the allocation of aggregate employment is likely to be further distorted. Even if the tax reform raises total employment, economic efficiency may be reduced because labour is reallocated from high-productive to low-productive jobs. Opportunities for on
Keywords: 330; the